Factors Affecting Land Conversion From Rice Plants to Lime Plants in Watabenua Village Landono District - Maulana, Rimat; Yunus, Lukman; Fyka, Samsul Alam (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
This study aims to determine what factors influence land conversion from lowland rice plantations to lime plantations in Watabenua Village, Landono District. The population in this study were all farmers who had converted land in Watabenua Village, Landono District, South Konawe Regency, and as many as 33 people, where all were used as samples by the census method 33 respondents. The analytical method used is multiple linear regression analysis. The results of this study are the factors that affect the conversion of land from lowland rice plantations to lime plantations in Watabenua Village are the cost of citrus production. In contrast, the factors that do not affect land conversion are rice income, the distance between irrigation water sources to rice fields, the price of another product, namely oranges.